A Conceptual Framework: Life Course Health Development and Partial Hand Loss - Alison L. Johnson (Scholarworks @ WMU, 2022)
Partial hand loss can be a profound source of disability with far-reaching economic and social consequences across the lifespan. Compared to other limb loss populations, perhaps surprisingly, the partial hand loss population experiences higher rates of whole-person impairment and disabling mental health conditions. Despite these known health disparities, the long-term health outcomes of the partial hand loss population are not adequately understood. Deepening understanding and preventing further disparity requires a multi-perspective approach examining factors contributing to health and well-being across the lifespan. This paper examines the partial hand loss population through two separate but overlapping lenses: population health and the life course approach. In addition, this paper presents an argument for the consideration of diverse perspectives and conceptual frameworks in the profession of occupational therapy. A case study is presented illustrating the clinical use of the Life Course Health Development (LCHD) framework as it relates to an individual with partial hand loss. Implications for occupational therapy and practice guidelines for integrating the LCHD framework are discussed.